2014
DOI: 10.1002/jor.22717
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between mechanical stress by finite element analysis and 18F‐fluoride PET uptake in hip osteoarthritis patients

Abstract: ABSTRACT:18 F-fluoride positron emission tomography ( 18 F-fluoride PET) is a functional imaging modality used primarily to detect increased bone metabolism. Increased 18 F-fluoride PET uptake suggests an association between increased bone metabolism and load stress at the subchondral level. This study therefore examined the relationship between equivalent stress distribution calculated by finite element analysis and 18 F-fluoride PET uptake in patients with hip osteoarthritis. The study examined 34 hips of 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Because changes in bone metabolism are present long before clear morphological signs, NaF-as well as FDG-PET can sooner identify and characterize early-stage OA, allowing for quicker treatment and closer monitoring of disease progression [58,59]. Furthermore, NaF demonstrates higher accuracy and sensitivity than 99m Tc-MDP and can reliably identify areas of high mechanical stress [60,61].…”
Section: Rheumatic Diseasesmentioning
confidence: 98%
“…Because changes in bone metabolism are present long before clear morphological signs, NaF-as well as FDG-PET can sooner identify and characterize early-stage OA, allowing for quicker treatment and closer monitoring of disease progression [58,59]. Furthermore, NaF demonstrates higher accuracy and sensitivity than 99m Tc-MDP and can reliably identify areas of high mechanical stress [60,61].…”
Section: Rheumatic Diseasesmentioning
confidence: 98%
“…18F-fluoride PET is a functional imaging modality used primarily to detect increased bone metabolism. A strong correlation was shown between the maximum standardized uptake value (bone remodelling acceleration) and maximum equivalent stress (mechanical stress) in hip OA, suggesting that 18F-fluoride PET may be able to detect increased bone metabolism at sites of stress concentration 16 . A study compared 18F-fluoride PET and MRI in evaluating early-stage hip OA and found 18F-fluoride PET could detect bone abnormalities earlier than MRI 17 .…”
Section: New Lessons From Nuclear Medicine Pet May Detect Early Bone mentioning
confidence: 98%
“…Baseline ultrasound detected gray-scale synovitis and power Doppler signals predicted radiographic progression of hand OA after 5 years 62 . Another study showed that ultrasound detected inflammatory features, including synovial thickening, effusion and power Doppler signal, especially when persistently 3 Radiography Hip and pelvic geometry are associated with the risk of compartment-specific knee OA Thomas GE, et al 49 Radiography Cam-type FAI and acetabular dysplasia predict development of hip OA and joint replacement High bone mineral density is associated with knee and hip OA Hardcastle SA, et al 4e6 Radiography High BMD Z scores are associated with increased prevalence of hip and knee OA, specifically osteophytosis Potential new approaches to examining joint structures Turunen M, et al 7 CT CBCT can measure volumetric BMD of cortical, trabecular, and subchondral trabecular bone Kokkonen HT, et al 8 CT Arthrographic images enables sensitive detection of cartilage lesions Riecke BF, et al 10 US Ultrasound score is reliable and valid in detecting knee OA Abraham AM, et al 14 US US demonstrates higher prevalence of osteophytes in hand and hip OA than radiographic studies Liukkonen J, et al 15 US Arthroscopic ultrasound imaging quantitatively evaluates articular cartilage Hirata Y, et al 16 Kobayashi N, et al 17 PET 18F-fluoride uptake is associated with mechanical stress in hip OA and can detect bone abnormalities earlier than MRI Ultrasonographic abnormalities correlate with clinical endpoints Hall M, et al 11 US Effusion and synovial hypertrophy are more common in knee OA, with severity correlating with radiographic severity of knee OA Birn J, et al 12 US Large joint effusions correlates with rapidly destructive hip OA Malas FU, et al 13 US Meniscal bulging is associated with radiographic joint space narrowing and KL grades What is new in magnetic resonance imaging? Morphological structural abnormalities predict clinical endpoints Sharma L, et al 19 MRI Cartilage damage, BMLs, meniscal tears, and meniscal extrusion are associated with prevalent frequent knee symptoms and/or incident persistent symptoms Roemer FW, et al 21 MRI Cartilage damage, BMLs, meniscal damage, synovitis and effusion predicted short-term need for knee joint replacement Eckstein F, et al 22 MRI Accelerated cartilage thickness loss is greatest closest to the time of knee replacement Composition of cartilage influences morphometry Crema MD, et al 25 MRI Poorer dermis endpoints are associated with increased cartilage thickness, potentially representing "cartilage swelling" Ukiah T, et al 26 MRI Diffusion tensor imaging can distinguish early cartilage damage Wyatt C, et al …”
Section: Mri and Ultrasound Findings Predict Progression Of Hand Oa Amentioning
confidence: 98%
“…Mononen et al58 also used finite element modelling to simulate cartilage degeneration using MRI data of knee joints from normal weight and obese OA patients. Using a functional imaging approach to reveal bone metabolism Hirata et al59 correlated changes in 18 F‐fluoride PET (positive‐emission tomography) uptake with stress distributions in the subchondral bone of coxo‐femoral joints from patients. These few examples suggest that there is still considerable work required to link clinical or functional measurements with in silico models for a number of OA‐associated tissues.…”
Section: Biology As a Systemmentioning
confidence: 99%